Assessment of TSH, FT4 and TPO-Ab Status During 1st Trimester of Pregnant Women in Dhaka City (Journal of Dhaka National Medical College & Hospital, 2020)
Background: Thyroid dysfunction may occur in pregnancy.Objective: To measure serum TSH, FT4 & TPO-Ab levels during 1st trimester of normal pregnant women.Method: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from July 2016 to June 2017. The ethical permission was taken from Institutional Ethics Committee (IEC) of SSMC. Total 60 female subjects, age ranged from 20 to 35 years were included in this study, among them 30 were apparently healthy pregnant women of 1st trimester (study group) and 30 were apparently healthy non-pregnant nulliparous women (control group). Serum TSH, FT4 and TPO-Ab levels were measured. The statistical analysis was done by Unpaired t-test.Results: In this study, mean serum TSH level was significantly (p